Intramolecular Charge Transfer in Ruthenium Complexes [Ru(acac)2(ciq)] with Ambidentate Camphoriminoquinone (ciq) Ligands - Filippou, Vasileios; Blickle, Svenja; Bubrin, Martina; Kaim, Wolfgang (Zeitschrift für anorganische und allgemeine Chemie (1950), 2021)
Reaction of [Ru(acac)2(MeCN)2], acac−=acetylacetonate, with N‐phenylcamphoriminoquinone (pciq) or the new N‐(2‐thiomethylphenyl)‐camphoriminoquinone (tciq) produces complexes [Ru(acac)2(pciq)] and [Ru(acac)2(tciq)] with N,O or N,S coordination and E or Z configuration at the C=N bond, respectively. Oxidation state assignments in comparison with classical iminoquinone ligands are based on structural data in connection with DFT calculations. Reversible oxidation yields complex ions [RuIII(acac)2(pciq)]+ and [RuIII(acac)2(tciq)]+ as characterized by EPR, IR and UV‐vis‐NIR spectroelectrochemistry.